Clinical and radiological results of treating lumbar spondylosis with cortical bone trajectory screws. Issue 44 (5th November 2021) - Bielecki, Mateusz; Kunert, Przemysław; Balasa, Artur; Kujawski, Sławomir; Marchel, Andrzej
Abstract : Abstract: The cortical bone trajectory screws technique (CBTT) is a popular minimally invasive spine surgery. Few studies have reported long-term outcomes. We aimed to evaluate the complication profile and long-term follow-up results of patients with lumbar degenerative disease treated with the CBTT. This retrospective analysis included the first 40 consecutive patients that underwent the CBTT. The indication for surgery was critical stenosis of the intervertebral foramen, which required removal of the entire intervertebral joint, on at least 1 side, during decompression. The last follow-up showed minimal clinically important differences in the numerical rating scale of leg pain, the numerical rating scale of back pain, and the Oswestry Disability Index, in 97%, 95%, and 95% of patients, respectively. Thirty-nine patients completed long-term radiological follow-up. Computed tomography demonstrated solid bone union on 47 (92%) operated levels, collapsed union on 2 (4%) levels, nonunion on 1 (2%) level, and 1 (2%) patient was lost to follow-up. Seven patients experienced complications (4 hardware-related). Three patients required 4 revision surgeries. The CBTT effectively achieved spinal fusion; over 90% of patients achieved clinical improvement at a mean follow-up of 4.4 years (range: 3–5.75 years).